Analisis Bauran Pemasaran Market Mix Terhadap Volume Penjualan pada Toko Unalala - Riskia Pratiwi Nur Amalia Hasnas; Dewi Putri Anjar Wulan; Fenty Y. Manuhutu (Musamus Journal of Business & Management, 2021)
This study aims to determine the effect of Marketing Mix on Sales Volume at Unalala Stores in Merauke Regency. To determine the effect of the Marketing Mix on Sales Volume at Unalala Stores in Merauke Regency, the population in this study is Unalala Store consumers whose number is unknown and a sample of 70 respondents. The calculation uses the Hair formula where the number of indicators is multiplied by 10 and uses the incidental sampling technique (coincidence). This study uses a quantitative approach and simple linear regression analysis with SPSS version 23 application. From the results of simple linear regression analysis, the equation Y = 7.891 + 0.482 (X). The results of hypothesis testing, namely the t-test, show that the Marketing Mix variable has a positive and partially significant effect on Sales Volume at Unalala Stores in Merauke Regency. It is proven by the tcount 4.076≥ t table 1.294 with a significant value of 0.000 <0.05 so that Ho is rejected and Ha is accepted. The value of R Square is 0.196, which means that the Marketing Mix variable affects the Sales Volume at the Unalala Store by 19.6% while the remaining 80.4% is influenced by other variables not examined in this study.